Vector mechanics for engineers : statics and dynamics - Beer, Ferdinand P. [ (Ferdinand Pierre)] , 1915-2003; Mazurek, David F. [ (David Francis)] (McGraw-Hill Education, 2016)
Continuing in the spirit of its successful previous editions, the eleventh edition of Beer, Johnston, Mazurek, and Cornwell's Vector Mechanics for Engineers provides conceptually accurate and thorough coverage together with a significant refreshment of the exercise sets and online delivery of homework problems to your students